Antibiogram of Escherichia coli Isolated from Avian Colibacillosis in Chitwan District of Nepal - Thapa, D.B.; Chapagain, A. (International Journal of Applied Sciences and Biotechnology, 2020)
A cross-sectional study was conducted at National Avian Disease Investigation Laboratory, Chitwan to determine antibiogram of Escherichia coli isolated from avian colibacillosis cases of broilers and layers in Chitwan. One hundred and sixty (95 from broilers and 65 from layers) liver samples were collected aseptically during postmortem. Samples were taken purposively from dead birds showing lesions perihepatitis, pericarditis, air-saculitis, omphalitis and egg peritonitis. Isolation and identification were made by examination of cultural characteristics of E. coli in MacConkey’s agar, Eosin methylene blue (EMB) agar, Gram’s staining and biochemical tests. Antibiogram of identified E. coli isolate was evaluated against six antibiotics of six different groups by disk diffusion method following CLSI guidelines. One hundred and three E. coliisolates (73 from broilers and 30 from layers) were isolated from one hundred and sixty samples. Highest resistance was observed against Ampicillin (100%) followed by Co-trimoxazole (86.40%), Doxycycline (46.60%), Levofloxacin (45.63%), Nitrofurantoin (26.21%) and Amikacin (10.68%). Nearly about all (96.12%) isolates from 103 isolated E. coli isolates showed multidrugs resistance to two or more than two antimicrobials. All multidrug resistance isolates showed 16 different patterns with each isolate being resistance to at least two drugs. The multiple antibiotic resistance indexing ranged from 0.2 to 0.8 and proportion of isolates with MAR index greater than 0.2 was 96.12%. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 52-60